Earth System Models Are Not Capturing Present‐Day Tropical Forest Carbon Dynamics. Issue 5 (20th May 2021) - Koch, Alexander; Hubau, Wannes; Lewis, Simon L.
Abstract: Tropical forests play a key role in absorbing carbon from the atmosphere into the land surface. Recent analyses of long‐term (1985–2014) forest inventory plots across the tropics show that structurally intact tropical forest are a large carbon sink, but that this sink has saturated and is projected to be in long‐term decline. Here we compare these results with estimates from the two latest generations of Earth System Models, Climate Modelling Intercomparison Project 5 (CMIP5) (19 models) and CMIP6 (17 models). While CMIP5 and CMIP6 are of similar skill, they do not reproduce the observed 1985–2014 carbon dynamics. The "natural" pan‐tropical carbon sink from inventory data is 0.99 Pg C yr −1 (95% CI 0.7–1.3, n = 614) between 2000 and 2010, the best sampled decade, double the CMIP6 multimodel‐mean of 0.45 Pg C yr −1 (95% CI 0.35–0.55). The observed saturating and declining sink is not captured by the models, which show modest increases in sink strength. The future (2015–2040) "natural" pan‐tropical sink from a statistical model driven by extrapolating past trends of its putative environmental drivers decreases by 0.23 Pg C per decade (95% CI 0.09–0.39) until the 2030s, while the CMIP6 multimodel‐mean under the climate change scenario closest to the statistical model project an increasing carbon sink (0.54 Pg C per decade; 95% CI 0.25–0.67). CMIP multimodel‐means reproduce the response of carbon gains from tree growth to environmental drivers, but the modeling of carbon losses from tree mortality does not correspond well to the inventory data. The model‐observation differences primarily result from the treatment of mortality in models. Plain Language Summary: The land surface is absorbing carbon from the atmosphere. Tropical forests play a key role in this carbon uptake. Recent long‐term analyses of forest inventory plots across Africa and Amazonia show that structurally intact tropical forest are a large carbon sink, but that this sink has recently saturated and is projected to be in long‐term decline. Earth System Models featuring in the Climate Modelling Intercomparison Project (CMIP) are used to project the influence of future climate change on this critical part of the global carbon cycle. As the current CMIP6 and its predecessor, CMIP5, directly inform future policy decisions through the IPCC Assessment Report and other channels, assessing the models' perfomance is crucial to better inform future climate policy. We show that the observed saturating and declining carbon sink is not captured by the CMIP models, which show modest increases in sink strength. The future pan‐tropical net sink from the statistical model decreases by 0.23 Pg C per decade until the 2030s, while CMIP6 multimodel‐means project an increasing carbon sink under all scenarios (0.01–0.03 Pg C per decade) bar one (−0.02 Pg C per decade). Reason for this is the treatment of vegetation mortality in the models. Key Points: Climate Modelling Intercomparison Project (CMIP) models do not reproduce observed saturation of carbon sink in intact tropical forests In modeling carbon gains and losses CMIP5 and CMIP6 are of similar skill CMIP6 models project an increase in tropical forest carbon sink under most future scenarios, the statistical model a decline in the sink